(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2011)
This article aims to explore the documentary principles as equivalents to the core matters proposed to the Information Science, as a way to promote the debate about its groundings. The study is justified because it considers that the perception over the identity crisis in Information Science is oriented by literature strongly based on specific axis, which engender partial views, incapable of constituting articulated parts of a whole. As methodology, it reviews the literature and discusses the history of Information Science, considering it prior to the emergence of this designation, and deals with its disciplinarity, presenting interdisciplinary frames, which are significantly consolidated. Besides, it studies the matter of the designations for the area. The study enables us to notice that the stir which involves the matter of identity of Information Science is not relevantly expressed in the literature and in the professional practices, which are oriented by Documentation, and which has presented, simultaneously, focus and density along the time. The history of Documentation permits us to question the discourses over the lack of consensus in Information Science and over the fragile central nature due to its technical dimension and to the supposed fluidity, intrinsic to its limits and borderline areas. It concludes that the documentary principles are a basic part of the grounds of the Information Science and are emblematic of its identity unit. link para o texto completo: http://www2.marilia.unesp.br/revistas/index.php/bjis/article/viewFile/48/275